Cognition and semiotics: The subject that thinks is the same one than means - González de Ávila, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
Both cognitive sciences and semiotics encourage a portrait of the subject, that is, of the human being as such. The former has a tendency to naturalize his traits, deriving them from biology; the second, to remember that the subject is so because he looks at himself in the mirror of culture, society and history. Beyond such divergences, it would be desirable for cognitive sciences and semiotics to pay mutual attention to each other, thus helping to balance their respective epistemological positions on subjectivity.
Keywords: Theory of the subject; reason; emotions; beliefs; values; thought and representation; enunciation and utterance